Municipalities and regions in locational competition – Relevant factors for success and political implications - Thomas Döring; Eithne Knappitsch; Birgit Aigner (Central European Public Administration Review)
Improving the business conditions of municipalities and regions, competitiveness concerning the location of new businesses and attraction of highly qualified labor are considered classical topics within regional economics and industrial location theory. Locational competition has intensified over recent years in the wake of the process of globalization, the general development towards a knowledge-based economy, and the dynamic of the international and the national division of labor. This analysis will be carried out in three steps. Firstly, traditional (e.g. industrial location theory) and newer economic approaches (e.g. new economic growth theory, innovative milieu approach etc.) will be outlined by means of discussing their insights and implications regarding the process of industrial location. This discussion shows that modern economies are increasingly developing into service and knowledge societies, in which factors formerly viewed as relevant within locational competition are becoming less important. Secondly, the paper analyzes the empirical evidence for these theoretical findings. According to existing empirical work, the evidence suggests that present studies mainly support the theoretically derived thesis of a shift in the classical ranking of locational factors. Finally, the paper seeks to explore conclusions concerning the design of local and regional economic policy at multiple governance levels.